Managing and mapping the history of collecting indigenous human remains*. Issue 3 (2nd July 2016) - Turnbull, Paul
Abstract: This article discusses the e-Scholarship Research Centre's contribution of informatics expertise and technology to a major three-year research project funded by the Australian Research Council (ARC). The project, Return, Reconcile, Renew, aimed to advance knowledge and understanding of the repatriation to Indigenous communities of ancestral human remains and related important cultural property. Project participants include three major Indigenous Australian community organisations (the Kimberley Aboriginal Law and Cultural Centre, Ngarrindjeri Regional Authority and the Torres Strait Regional Authority, university and Indigenous community-based researchers in Australia, Aotearoa/New Zealand and Northern America, the Australian Federal Government's Indigenous Repatriation Unit, and a number of cultural and research institutions nationally and internationally.